Development of Collaborative Peer-Based Authentic Assessment in Physics Learning - Nurudin, M.; Suharto, Toto; Bakri, Syamsul; Makruf, Imam (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study presents findings on developing collaborative peer-based authentic assessment in physics learning. This type of research is qualitative descriptive. The source of research data with secondary data is derived from data from SMK Muhammadiyah 1 Klaten. The data analysis involves collecting, organizing, interpreting, and drawing conclusions from qualitative research data. The research results show that the PCAA model is an assessment of the learning process that can improve higher-order thinking skills (HOTS) and can be applied to improve the quality of education. Collaborative skills, peer assessment, and authentic assessment can improve the quality of education. The Peer Collaborative-Authentic Assessment (PCAA) model assesses Higher Order Thinking Skills (HOTS) learning. HOTS learning can improve education quality, so that the PCAA model can improve the quality of education.